Pirates of the Caribbean the curse of the Black Pearl - Bruckheimer, Jerry; Elliott, Ted.; Rossio, Terry; Verbinski, Gore.; Depp, Johnny; Rush, Geoffrey, 1951-; Bloom, Orlando, 1977-; Knightley, Keira, 1985-; Davenport, Jack, 1973-; Pryce, Jonathan; Arenberg, Lee.; Crook, Mackenzie, 1971-; et al. (Burbank, CA : Distributed by Buena Vista Home Entertainment, Burbank, CA : Distributed by Buena Vista Home Entertainment, 2003)
The roguish yet charming Captain Jack Sparrow's idyllic pirate life capsizes after his nemesis, the wily Captain Barbossa, steals his ship, the Black Pearl, and later attacks the town of Port Royal. Captain Barbossa kidnaps the governor's beautiful daughter, Elizabeth. In a gallant attempt to rescue her and recapture the Black Pearl, Elizabeth's childhood friend Will Turner joins forces with Jack. What Will doesn't know is that a cursed treasure has doomed Barbossa and his crew to live forever as the undead.
Title from container.
Special features: 19 deleted and alternate scenes; "Walt Disney's Wonderful World Of Color"; "Moonlight serenade" scene progression; image galleries; Disneyland Pirates virtual reality viewer; "Moonlight becomes ye" effects studio; "Dead men tell no tales" -- the history of the attraction; Pirates of the caribbean attraction image gallery; ScriptScanner(TM); storyboard viewer; blooper reel; multiple audio commentaries: Gore Verbinski And Johnny Depp; Jerry Bruckheimer: Keira Knightley and Jack Davenport; writers Ted Elliott & Terri Rossio and Stuart Beattie and Jay Wolpert; "An epic at sea: the making of PIRATES"; Below deck: an interactive history of Pirates; "Fly on the set" featurettes; diary of a Pirate; diary of a ship; producer's photo diary with Jerry Bruckheimer.
Director of photography, Dariusz Wolski ; editors, Craig Wood, Stephen Rivkin, Arthur Schmidt ; music, Klaus Badelt ; costume designer, Penny Rose ; production designer, Brian Morris ; visual effects and animation, Industrial Light & Magic.
Johnny Depp, Geoffrey Rush, Orlando Bloom, Keira Knightley, Jack Davenport, Jonathan Pryce, Lee Arenberg, Mackenzie Crook, Damian O'Hare.
MPAA rating: PG-13; for action/adventure violence.
DVD, produced for region 1 (North America); user must have a DVD player that will play region 1 DVDs; DTS 5.1 digital surround sound, 5.1 Dolby digital.
Keywords: Pirates -- Drama; Sailing ships -- Drama; Adventure and adventurers -- Drama; Feature films; Adventure films; Video recordings for the hearing impaired